2018
DOI: 10.1038/s41598-018-21336-7
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin protects cochleae from damage by high-level noise

Abstract: Exposure to noise and ototoxic drugs are responsible for much of the debilitating hearing loss experienced by about 350 million people worldwide. Beyond hearing aids and cochlear implants, there have been no other FDA approved drug interventions established in the clinic that would either protect or reverse the effects of hearing loss. Using Auditory Brainstem Responses (ABR) in a guinea pig model, we demonstrate that fluvastatin, an inhibitor of HMG-CoA reductase, the rate-limiting enzyme of the mevalonate pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 76 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…In rats, atorvastatin was able to prevent noise-induced SNHL [90]. The same was found in mice [91] and more recently in guinea pigs [92]. In a prospective study of 84 hyperlipidemic patients and audiological assessment before and 6 months after commencement of a statin, a significant reduction of the hearing threshold at 6000 Hz was found and a significantly improved speech discrimination as well as a significant reduction in tinnitus frequency, duration, and severity and degree of annoyance [93].…”
Section: Resultsmentioning
confidence: 78%
“…In rats, atorvastatin was able to prevent noise-induced SNHL [90]. The same was found in mice [91] and more recently in guinea pigs [92]. In a prospective study of 84 hyperlipidemic patients and audiological assessment before and 6 months after commencement of a statin, a significant reduction of the hearing threshold at 6000 Hz was found and a significantly improved speech discrimination as well as a significant reduction in tinnitus frequency, duration, and severity and degree of annoyance [93].…”
Section: Resultsmentioning
confidence: 78%
“…This is consistent with the known mechanism of action of nitrogencontaining bisphosphonates, which act on the mevalonatecholesterol pathway by inhibiting FPPS (Figure 5). Supporting a role for the mevalonate pathway, previous work has shown that inhibiting HMG-CoA reductase, which is further upstream in the mevalonate pathway, protected against noise-induced hearing loss in guinea pigs and mice (Park et al, 2012;Richter et al, 2018). Cholesterol metabolism is important in neurodegenerative diseases and strongly associated with SNHL (Malgrange et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…A recent interview‐based report showed that doctors tended to consider alternative medicines if ototoxicity is detected in patients 7 . However, ototoxic drugs are still widely used in most developing countries, due to economic conditions and no prescription‐restriction 8 . Therefore, reducing the ototoxicity of clinical drugs while ensuring their therapeutic efficacy is a problem that needs to be solved at present.…”
Section: Introductionmentioning
confidence: 99%